Gaya hidup digital pemoderasi persepsi dan sikap terhadap keputusan menggunakan lebih dari 1 (satu) telepon genggam - Melifia Liantifa; Ferry Siswadhi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of the research was to investigate the moderating effect of digital life style on the relationship between perseption and attitude on consumer decision to used more than one handphone. The research of sample was Kerinci public used more than one handphone, working dan have income using purposive sampling method. Data was colected through questionnaire with Likert’s scale which analysis using deskriptive qualitative and quantitative as test of validity and reliability, average score and TCR, coefisien of determination, hypothesis testing performs moderated regression analysis (MRA) by processing the data using SPSS 19.0 for windows. The result of analysis found that: a) Perseption not found significantly influeced consumer decision to used more than one handphone. b) Attitude and digital life style was found significantly influenced consumer decision to used more than one handphone, c) Digital life style was found as moderating variable between perseption and attitude of decision to used more than one handphone.